Dimethyl sulfate and diisopropyl sulfate as practical and versatile O-sulfation reagents - Shuaishuai Yue; Guoping Ding; Ye Zheng; Chunlan Song; Peng Xu; Biao Yu; Jiakun Li (Nature Communications, 2024)
Abstract O-Sulfation is a vital post-translational modification in bioactive molecules, yet there are significant challenges with their synthesis. Dialkyl sulfates, such as dimethyl sulfate and diisopropyl sulfate are commonly used as alkylation agents in alkaline conditions, and result in the formation of sulfate byproducts. We report herein a general and robust approach to O-sulfation by harnessing the tunable reactivity of dimethyl sulfate or diisopropyl sulfate under tetrabutylammonium bisulfate activation. The versatility of this O-sulfation protocol is interrogated with a diverse range of alcohols, phenols and N-OH compounds, including carbohydrates, amino acids and natural products. The enhanced electrophilicity of the sulfur atom in dialkyl sulfates, facilitated by the interaction with bisulfate anion (HSO4 -), accounts for this pioneering chemical reactivity. We envision that our method will be useful for application in the comprehension of biological functions and discovery of drugs.